Semántica léxica y estructuración aspectual/eventiva: telicidad, perfectividad y delimitación en el análisis de las cópulas españolas - Mangialavori Rasia, Ma. Eugenia (2016)
Spanish copulas have inspired a vast amount of studies involving a significant number of technical concepts in their description. Against this background, we concentrate on the need to refine the technical parameters used, focusing on the linguistic domains where they are encoded and on the distinction between lexical and constructional semantics. Building on specific tests, we propose that ser and estar: (i) depart from both the standard notion of copula (semantically trivial verb) and of stative verb (lacking temporal structure) and are at least ambiguous as for the eventive type of construction they render; (ii) that many properties observed in the literature do not actually ensue from to the copula per se, but rather from the construction they head; (iii) and that the parameter boundedness best captures their situation, as long as it is conceived as a different semantic property, logically distinguishable from perfectivity telicity.